Status, Pemberdayaan Perempuan dan Penggunaan Kontrasepsi: Metode Khusus Perempuan Versus Metode Pasangan - Elfrida Zoraya; I. G. A. A Karishma Maharani Raijaya (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Women’s autonomy is considered important in reproductive health care and treatment options on seeking behavior. The improvement in various dimensions of women’s status and empowerment is expected to increase their role in decision making concerning fertility-related issues. This paper aims to analyze the association between women’s status and empowerment and contraceptive use - and of how these associations are mediated by socio-economic and demographic statuses. This study use cross sectional data from the 2017 Indonesia DHS. This study analyzed on 19,159 married women who currently either using any form of contraceptive using logit regression. Contraceptive use was categorized as either women-only or couple methods on the basis of whether a method requires the awareness of, or some support and cooperation from the husband. The result shows that women’s status had strongly positive associations with couple methods to female-only methods. Yet some empowerment dimension was less important in determining contraceptive use. Effort needs to be made on promoting gender roles and to educate women with particular focus on highly effective contraceptive methods.